Pengaruh Strategi Pembelajaran Klarifikasi Nilai Dan Locus of Control Terhadap Kemampuan Berpendapat Mahasiswa - Sukisno, Sukisno (Jurnal Varidika: Varia Pendidikan, 2014)
This study aimed to examine the effect of VCT instructional strategies (pair group and small groups of 4-7 students) and studentâs locus of control on learning outcomes in civics courses. The aim of this study was to determine the main effects and the interaction effect of treatment and moderator variables on Civics Education learning outcomes. This quasi-experimental study used a factorial design with posttest non-equivalent control group design. Subjects of this study were the second semester students, Economic department, 2012-2013 academic year. The subjects were 74 students, consisting of 36 students from class A for the experimental class and 38 students from class B as a control class. The results of this study indicates that 1) there is significant differences of argument ability of the students in Civics between the groups of students studying with the pair group VCT learning strategy and those with VCT small groups of 4-7 students, 2) the argument ability of Civics Education learning students in Civics course, between groups of students with internal locus of control and those with external locus of control, significantly different, and 3) instructional strategies and locus of control shows the interaction effect on arguing ability in Civics.